Designing a techonolgy for the elderly: Elderband and elderalert - Arshad, Noreen Izza; Goh, Yu Chen; Mehat, Mazlina (2016)
The number of adults aged between 60 and older experiencing fall is alarming.Therefore prevention of fall among elderly assisted by technology is this research priority.There are various fall detection devices and smartphone applications available in the market which all have the same aim, acting as a medium to notify the emergency contacts of the location and time when user falls. The users of those devices and applications are mainly elderly who may have suffered from falls or have difficulties which may lead to more serious injuries.However, there are a number of constraints posed by these available fall detection devices and applications. The fall detection devices are expensive and some require monthly subscription.The devices need to be carried with the user at all times to ensure the fall can be detected.Therefore, this research aims to minimize the mentioned disadvantages with the introduction of ElderBand and ElderAlert. ElderBand is a smart wearable which is lightweight and can be worn by user at all times.ElderAlert is a smartphone application which enables notifications to the emergency contacts in case of a fall. Both ElderBand and ElderAlert are connected via Bluetooth for the fall detection system to work.ElderBand transmit acceleration data continuously to ElderAlert to estimate a fall. It then notifies the emergency contact when a fall is detected. This research provides ideas on how technology could be designed for better quality of life for the elderly.